2021
DOI: 10.3389/fmicb.2021.670535
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Narrow-Spectrum Protein Antibiotics to the Lower Gastrointestinal Tract in a Murine Model of Escherichia coli Colonization

Abstract: Bacteriocins are narrow-spectrum protein antibiotics that could potentially be used to engineer the human gut microbiota. However, technologies for targeted delivery of proteins to the lower gastrointestinal (GI) tract in preclinical animal models are currently lacking. In this work, we have developed methods for the microencapsulation of Escherichia coli targeting bacteriocins, colicin E9 and Ia, in a pH responsive formulation to allow their targeted delivery and controlled release in an in vivo murine model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Recent work has demonstrated that E. coli ‐specific protein antibiotics known as colicins can be successfully formulated for targeted oral delivery and controlled release to reduce AIEC LF82 levels in an in vivo murine model of E. coli colonisation. In the future, it is possible that concomitant therapy with such antimicrobial agents and effective dietary therapies, like EEN, will have better synergistic effectiveness than each of these therapeutics in isolation 145 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has demonstrated that E. coli ‐specific protein antibiotics known as colicins can be successfully formulated for targeted oral delivery and controlled release to reduce AIEC LF82 levels in an in vivo murine model of E. coli colonisation. In the future, it is possible that concomitant therapy with such antimicrobial agents and effective dietary therapies, like EEN, will have better synergistic effectiveness than each of these therapeutics in isolation 145 …”
Section: Discussionmentioning
confidence: 99%
“…In the future, it is possible that concomitant therapy with such antimicrobial agents and effective dietary therapies, like EEN, will have better synergistic effectiveness than each of these therapeutics in isolation. 145 In conclusion, there are preclinical and some clinical trial data to propose that E. coli and other Enterobacteriaceae interact with certain dietary components in CD to promote gut inflammation. Nonetheless, for some dietary components, patterns or therapies the evidence is inconsistent and currently none of these studies can prove a causal relationship.…”
Section: E Xclus Ive Enter Al N Utriti On (Een) and Novel D Ie Tary T...mentioning
confidence: 99%
“…Another study demonstrated that microcapsule delivery of the active form of colicin Ia reduced E. coli colonisation in murine models [225]. Engineering of chimeric proteins and use of cocktails of different toxins could provide a greater spectrum of activity and reduce the risk of resistance developing in target bacteria [226].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when injected into the bloodstream of mice, pyocin S5 was observed to retain its functionality and to improve mouse survival to Pseudomonas infections [224]. Another study demonstrated that microcapsule delivery of the active form of colicin Ia reduced E. coli colonisation in murine models [225]. Engineering of chimeric proteins and use of cocktails of different toxins could provide a greater spectrum of activity and reduce the risk of resistance developing in target bacteria [226].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a similar study was published describing the use of encapsulated colicins for the eradication of E. coli in mice [36.] Colicins encapsulated into hydrogel particles were shown to be released from the protective coat at pH above 5 and reduce colonizing E. coli numbers in the gut and in feces, although complete eradication of the pathogen was not achieved [ 39 ]. Consequently, further research on klebicin formulation for the most efficient release in the lower intestinal tract is necessary.…”
Section: Discussionmentioning
confidence: 99%